Analytical Method Analysis based on Eccentric Load of Slewing Bearing - Weiting Zeng; Manyi Chen (Jixie chuandong)
The blast furnace top gearbox is the key equipment of the stock distribution of blast furnace. The quality of the blast furnace top gearbox is directly related to the quality and efficiency of the blast furnace iron making. The upper slewing bearing is an important bearing component of the blast furnace top gearbox, which connects the fixed end and the moving end. If the frame or the slewing bearing is slighted inclination, the central axis line of the rotating body will be deviated from the geometric central axis line, which causing the unbalance loading of the slewing ring. The eccentric slewing bearing is taken as the research object, the load calculation and equivalent are carried out. Then, the mathematical model is established and the analytic method is used to calculate the load distribution and deformation of the rolling elements inside the slewing bearing. The theoretical support for slewing bearings to withstand eccentric load research is provided.